Associations between child mental health, carer worry and help-seeking. (September 2022) - Liverpool, Shaun; Edbrooke-Childs, Julian
Carers may not always express child mental health concerns to health professionals. Therefore, identifying factors delaying help-seeking is important. The aim of this study was to examine the relationship between carer affect and help-seeking. In a secondary analysis of data collected from school-aged children ( N = 1, 857, mean age = 9.85 years, 51% female), we used logistic regression to examine the associations between carer worry, help-seeking and child mental health. Regarding worry, higher levels of emotional problems (OR = 1.42, 95% CI = 1.33–1.52), conduct problems (OR = 1.24, 95% CI = 1.12, 1.36), peer problems (OR = 1.17, 95% CI = 1.05–1.27) or functional impairment (OR = 1.37, 95% CI = 1.2–.56) were associated with higher levels of carer worry. Regarding help-seeking, higher levels of functional impairment were associated with higher levels of help-seeking (OR = 1.51, 95% CI = 1.09–2.11). After controlling for mental health problems, carers who reported being worried about their child's mental health were less likely than other carers to seek help (OR = 0.13, 95% CI = 0.05–0.35). Knowledge of these factors may inform early interventions. Alongside implications for future research and practice, limitations of the study are discussed.